The Implementation of Character Education as an Effort to Realise the Profile of Pancasila Students Based on Local Wisdom - Sukirno Sukirno; Juliati Juliati; Tengku Muhammad Sahudra (AL-ISHLAH: Jurnal Pendidikan, 2023)
A single-character education acts as a form of learning that refers to the development and strengthening of children's behaviour as a whole, which is based on a certain value or moral referred to by the school. Therefore, character education is one of the efforts that can be done. One of the character education is through the Pancasila Student Profile. The Pancasila Student Profile has been used as one of the visions and missions of the Ministry of Education and Culture. This study aims to find out related to the implementation of strengthening the value of character education in realising the profile of Pancasila students' independent, critical reasoning, noble character, creativity, global diversity and cooperation. Then to find out the school's efforts in the process of strengthening character education based on local wisdom in instilling religious character, independence and integrity. The methods used in the research descriptive methods are qualitative. The results of this study show a lack of knowledge in the development of education regarding the profile of Pancasila students, and the implementation of strengthening character education has been carried out, such as instilling religious character, independence and integrity. The conclusion of this study has a positive impact on schools in knowing the profile of Pancasila students, and instilling character education has a positive impact on students who are included in local wisdom carried out in the learning process at school.